Оцінка гіполіпідемічного ефекту мультибіотика симбітер у хворих на цукровий діабет 2-го типу з неалкогольною жировою хворобою печінки - Михальчишин, Г. П.; Боднар, П. М.; Янковський, Д. С.; Берегова, Т. В.; Кобиляк, Н. М. (Clinical Endocrinology and Endocrine Surgery, 2013)
We examined 72 patients with T2D and NAFLD. All patients were divided into 2 groups. The main group (n=45) received oral antidiabetic therapy and multiprobiotic "Symbiter" within 30 days. Patients of comparison group (n=27) received only hypoglycemic drugs. All patients underwent determination of lipid parameters before and after treatment. We observed reduction in total cholesterol level on 4.8% (p=0.001), non-HDLC on 6.9% (p<0.001), LDL-C on 7.2% (p=0.003) and triglycerides on 10 6% (p = 0.010) after the course of multiprobiotic "Symbiter". Significant changes on HDLC level (p=0.085) in main group and for all lipid parameters on the comparison group after treatment were not found.